Peace and Pollution: An Examination of Palestinian—Israeli Trans-Boundary Hazardous Waste Management 20 Years after the Oslo Peace Accords. Issue 1 (April 2013) - Alleson, Ilan; Levin, Jamie; Brenner, Shmuel; Al Hmaidi, Mohammad Said
As part of the Oslo Accords, Israel and the Palestinian Authority agreed to jointly manage issues of environmental concern according to internationally recognised standards. The purpose of this paper is to qualitatively evaluate the outcomes of the Palestinian–Israeli Oslo environmental peace agreements regarding trans-boundary hazardous waste management. Hazardous waste is an area of particular importance given the potential for inefficient management to impact on public health and shared ecological resources. Although the environmental negotiations that took place within the framework of the Oslo Accords can be seen as a significant milestone for environmental cooperation, many objectives were never achieved. Ultimately, both parties were left with suboptimal trans-boundary management, in practice, because broader political disputes derailed cooperation in many technical spheres. This outcome can be attributed to four main factors: Israeli security concerns, territorial disputes, logistical ambiguities and Palestinian institutional constraints. The outcomes of the environmental agreements challenge neo-functionalist approaches to peacebuilding at the inter-state level. Given the risks environmental concerns pose to both sides, new models are needed that disentangle the management of immediately shared environmental challenges from the ongoing conflict.